VIZANTIAN LAW AS A NURSERY GARDEN OF LEGAL TRANSPLANTS WITH A SPECIAL REVIEW ON THE DUSHAN’S CODE - Macura, Milan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Byzantium, or often used term Byzantine Empire, is an expression used to indicate the state of creation that existed in the period from the 4th century until the fifteenth century, more precisely in 1453, and the fall of Constantinople as a result of the Ottoman conquest. Regardless of the historical discusions and opinions about the creation of Byzantium, in this scientific work as the beginning of the Byzantine Empire was taken 11 May 330, the date when Constantine the Great inaugurated (Greek ΝέαῬώμη, lat.NovaRoma) at the place where the Greek colony of Vizantas was spreading. In my view, the paper will analyze the influence of Byzantine law on the further development of rights in the world as well as the temporal continuity and the development of the Byzantine law itself that relies on Roman law.